The Puerto Rican Experience An Educational Research Study. - Puerto Rican Congress of New Jersey, Trenton; Puerto Rican Congress of New Jersey, Trenton ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1974)
In the fall of 1972, superintendents and principals in 21 school district with significant Puerto Rican enrollment were interviewed. The interviews (usually lasting over three hours) focused on the educators' attitudes toward Puerto Ricans as a people; their perceptions of the educational needs of Puerto Rican youngsters; views on accountability, assimilation versus cultural pluralism, bilingual/bicultural education, and parental involvement. Among the findings were the following: While 30 percent of the educators indicate it is methodologically unsound to evaluate the educational development of children with a language barrier (primary language of communication being different from the language of instruction) in the same manner as for children who speak and understand English fluently, all 21 districts do so. Only 13 percent of the educators indicated that they were trying to correct this procedure, despite limited resources, by using bilingual test monitors and reportedly intensive Spanish-speaking personnel recruitment. Seventy percent of the administrators stated that they agreed with accountability, but only if it were shared equally by parent, student, teacher, principal, superintendent, board, funding source, and 10 percent even included in the school custodian. (Author/JM)
Sponsoring Agency: Office of Education (DHEW), Washington, DC.
Contract Number: OEG-0-72-1110.
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Accountability; Acculturation; Administrator Attitudes; Biculturalism; Bilingual Education; Cultural Pluralism; Educational Needs; Parent Participation; Principals; Puerto Ricans; School Administration; Spanish Speaking; State Surveys; Superintendents; New Jersey; Reports, Research